Monetary policy implementation frameworks: A comparative analysis - Antoine Martin; Cyril Monnet (Federal Reserve Bank of New York, 2008)
We compare two stylized frameworks for the implementation of monetary policy. The first framework relies only on standing facilities, and the second one relies only on open market operations. We show that the Friedman rule cannot be implemented in the first framework, but can be implemented using the second framework. However, for a given rate of inflation, we show that the first framework unambiguously achieves higher welfare than the second one. We conclude that an optimal system of monetary policy implementation should contain elements of both frameworks. Our results also suggest that any such system should pay interest on both required and excess reserves.
Keywords: E52; E58; E59; 330; Monetary policy implementation; standing facilities; open market operations; Geldpolitik; Offenmarktpolitik; Theorie